Review on Surfactant Modified Zeolites as slow Release fertilizer - Sabiya Khan; Sheikh Abdul Majid (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Zeolites could be the potential solution of some major problems in agriculture including pollution due to excessive use of fertilizers and economic drain due to the same. Ion exchange of zeolites can be used to load agents as well as release them and the high ion exchange capacity improves the loadings of agents. Because of these properties, zeolites have been used for controlled release of fertilizer components. Zeolites added to fertilizers help to retain nutrients and therefore improving the long term soil quality by enhancing its absorption ability. The surfactant modified zeolites (SMZ) could be used as carriers in controlled release formulations of fertilizer with higher affinity for anions to decrease its contamination potential.